The end of the City of Gold? : industry and economic crisis in an Italian jewellery town - Fontefrancesco, Michele Filippo (Cambridge Scholars Publishing, 2013)
How does Europe's economic crisis affect the ways in which industry and entrepreneurship are experienced on a grassroots level? The book offers an answer to this question by exploring the Italian jewellery town of Valenza and the downturn of its principal industry. Through the experiences of its inhabitants, the study investigates the social role that jewellery production had in Valenza and provides an ethnographic account of the crisis the city endures. This analysis delves into the relation ...